Phenotypic and molecular diversity of Meyerozyma guilliermondii strains isolated from food and other environmental niches, hints for an incipient speciation. (June 2015) - Corte, Laura; di Cagno, Raffaella; Groenewald, Marizeth; Roscini, Luca; Colabella, Claudia; Gobbetti, Marco; Cardinali, Gianluigi
Abstract: Meyerozyma guilliermondii is a yeast species widely isolated from several natural environments and from fruit; in medical microbiology it is known as the teleomorph of the opportunistic pathogen Candida guilliermondii, which causes about 2% of the human blood infections. This yeast is also promising in a variety of biotechnological applications as vitamins production and post-harvest control. The question if isolates from different sources are physiologically and genetically similar, or if the various environments induced significant differences, is crucial for the understanding of this species structure and to select strains appropriate for each application. This question was addressed using LSU and ITS sequencing for taxonomic assignment, i-SSR (GACA4 ) for the molecular characterization and FTIR for the metabolomic fingerprint. All data showed that fruit and environmental isolates cluster separately with a general good agreement between metabolomics and molecular analysis. An additional RAPD analysis was able to discriminate strains according to the isolation position within the pineapple fruit. Although all strains are members of the M . guilliermondii species according to the current standards, the distribution of large variability detected suggests that some specialization occurred in the niches inhabited by this yeast and that food related strains can be differentiated from the medical isolates. Highlights: 96 Meyerozyma guiliiermondi strains, from various sources, were identified. Strains were characterized with different molecular tools and by FTIR fingerprint. Fruit strains clustered separately from environmental and medical isolates. RAPD discriminated pineapple strains according to their origin within the fruit. An incipient specialization appears to be induced by diverse habitats.